Comparasion of physiology characteristics of difference position in elite male handball players - Xiaobin, W. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
INTRODUCTION: Handball players have several field positions, but the physical abilities of players in different positions may vary and therefore need to be treated differently. METHODS: 25 elite male handball players (age:22.6±3.7, height: 191.3±6.4cm, weight: 90.9±13.2kg) participated in the study, tested twelve physiological and physical fitness indexes of the players, and compared the differences between different position(goalkeeper, pivot, back and wing) by ANOVA with Bonferroni post-hoc test RESULTS: There were no difference with height, weight, vertical jump height, 30m sprint, YoYo test, pull-up, 60°·s-1 isokinetic muscle strength test in different position (p > 0.05). There were group differences in the 1RM squat and bench press (p*0.05). CONCLUSION: No difference in height, weight, speed, endurance, explosive power, slow isometric muscle strength between position handball players and there is a difference between the maximum strength of deep squat and bench press. Practitioners can use the result as a reference for training, but should also be aware of the small sample size in this study.